The Effect of Mudharobah Financing, Musyarokah Financing, and Murabahah Financing on BPRS Profitability in Indonesia - Rizqi, Muhamad Nur; Prasetia, Angga; Rasiman, Rasiman (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
This study aims to determine the effect of mudharobah financing, musyarokah financing and murabahah financing on Sharia People's Credit Banks registered with the Indonesian Financial Services Authority (OJK) in the 2017-2021 period. Data is obtained from Sharia Banking Statistics which is a collection of Sharia Commercial Banks and Sharia Units throughout Indonesia, so that what is done is sampling a number of populations. This type of research is descriptive quantitative, which is processed using multiple linear regression with the help of NCSS 2021. The results showed that mudharobah and murabahah financing had no effect on profitability, while musyarokah financing had an effect on profitability.